The Outlook for the UNECE Forest Sector in a Changing Climate - United Nations Economic Commission for Europe (United Nations, 2023)
The Forest Sector Outlook Study 2020-2040 (FSOS) for the UNECE region provides information that supports decision-making by showing the possible medium and long-term consequences of specific policy choices and structural changes, using scenario analyses whenever possible. The study is the first to cover the entire UNECE region and provides results for the main UNECE subregions of Europe, North America and the Russian Federation. This Discussion Paper presents the detailed research, analysis and findings that were used to develop Chapter 4 of the UNECE/FAO Forest Sector Outlook Study 2020-2040. The study takes a pragmatic, transparent and objective approach to answering these key questions, sometimes using a modeling approach. It enables stakeholders to evaluate the long-term consequences of policy choices.